Development of design tools to reduce design complexity - Ng, Collin Cheng Chow. (2010)
In an increasingly competitive, intensive and globalised market, the need to diversify is greater than ever before. To remain strong in competition, companies combined product model variety and high rates of technological changes to meet the needs and demands of the consumer market. However, implementing these new developments increase the design complexity in products or systems. Design complexity caused by design changes, design uncertainty and poor control measures usually lead to redesigning which has a huge impact on the schedule, cost and quality of the product.